A phosphor sheet and a backlight system providing wider color gamut for LCDs. Issue 8 (3rd February 2015) - Ito, Yasushi; Hori, Tomomitsu; Kusunoki, Tsuneo; Nomura, Hiroshi; Kondo, Hirofumi
Abstract: SrGa2 S4 :Eu and CaS:Eu phosphors are useful to provide a wider color gamut to LCDs since their emissions are narrower, but they easily react with moisture. The phosphor sheet containing them was developed. The moisture barrier layers on it can separate them from a humid atmosphere. The LCD with the phosphor sheet could realize the wider color gamut of 90% NTSC‐xy, while the color gamut of the original LCD with the white LEDs containing YAG:Ce phosphor was 71% NTSC‐xy. The improvement of the brightness of the LCD with the phosphor sheet was studied. Encapsulates with a greater curvature on blue LEDs used with the phosphor sheet can increase the brightness. The brightness of the LCD with the phosphor sheet and blue LEDs with the spherical encapsulates of which the curvature = about 0.7 was estimated to reach to 85% of that of the original LCD. The simpler phosphor sheet with the aluminum film edge seals was also developed. It was confirmed that it has sufficient reliability during storage and operation at high temperature and high humidity and there is no difference in its reliability between the edge area and the center area. The importance of the moisture barrier layers which protect the SrGa2 S4 :Eu and CaS:Eu phosphors was confirmed. The phosphor sheet with the moisture barrier layers had better reliability than that with the PET layers.